Early mortality after implantable cardioverter defibrillator: Incidence and associated factors. (15th February 2020) - Garcia, Rodrigue; Boveda, Serge; Defaye, Pascal; Sadoul, Nicolas; Narayanan, Kumar; Perier, Marie-Cécile; Klug, Didier; Fauchier, Laurent; Leclercq, Christophe; Babuty, Dominique; Bordachar, Pierre; Gras, Daniel; et al.
Abstract : Background: According to guidelines, implantable cardioverter defibrillator (ICD) candidates must have a "reasonable expectation of survival with a good functional status >1 year". Identifying risk for early mortality in ICD candidates could be challenging. We aimed to identify factors associated with a ≤1-year survival among patients implanted with ICDs. Methods: The DAI-PP program was a multicenter, observational French study that included all patients who received a primary prevention ICD in the 2002–2012 period. Characteristics of patients who survived ≤1 year following the implantation were compared with those who survived >1 year, and predictors of early death determined. Results: Out of the 5539 enrolled patients, survival status at 1 year was known for a total of 5, 457, and overall 230 (4.2%) survived ≤1 year. Causes of death were similar in the two groups. Patients with ≤1-year survival had lower rates of appropriate (14 vs. 23%; P = 0.004) and inappropriate ICD therapies (2 vs. 7%; P = 0.009) than patients who lived >1 year after ICD implantation. In multivariate analysis, older age, higher NYHA class (≥III), and atrial fibrillation were significantly associated with ≤1-year survival. Presence of all 3 risk factors was associated with a cumulative 22.63% risk of death within 1 year after implantation. Conclusions: This is the largest study determining the factors predicting early mortality after ICD implantation. Patients dying within the first year had low ICD therapy rates. A combination of clinical factors could potentially identify patients at risk for early mortality to help improve selection of ICD candidates. Highlights: Amongst patients with ICD for primary prevention, 4.2% survived less than one year. This prevalence was close to those documented in RCTs (MADIT II, SCD Heft). Age >70yo, NYHA class ≥ III and AF were associated with ≤1-year survival. Patients with all these 3 risk factors had a 22.63% risk of ≤1-year survival.